1996
DOI: 10.1111/j.1151-2916.1996.tb08533.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Phase Relations of Aluminum‐Substituted Calcium Silicate Hydrate

Abstract: The structures of aluminum‐substituted calcium silicate hydrate (C‐S‐H) forming in a series of aqueous suspensions formulated with colloidal silica, reactive alumina, and lime and aged for 1 year have been studied using 29Si and 27Al magic angle spinning nuclear magnetic resonance spectroscopy (with and without cross polarization (CP)), solution pH, electron microscopy, and X–ray diffraction. As in earlier work dealing with the nature of C‐S‐H in the system CaO‐SiO2H2O2 two aluminum‐substituted C‐S‐H phases, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Measurements were conducted under magic angle sample spinning (MAS) up to 5 kHz in zirconia rotors with a Varian 7 mm probe. 12 The Hartmann-Hahn match condition for 1 H- 27 Al CP was adjusted with a sample of kaolinite. Kaolinite was used as a secondary standard for chemical shift (Ϫ91.2 ppm with respect to TMS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements were conducted under magic angle sample spinning (MAS) up to 5 kHz in zirconia rotors with a Varian 7 mm probe. 12 The Hartmann-Hahn match condition for 1 H- 27 Al CP was adjusted with a sample of kaolinite. Kaolinite was used as a secondary standard for chemical shift (Ϫ91.2 ppm with respect to TMS).…”
Section: Methodsmentioning
confidence: 99%
“…(3) 27 Al NMR Spectroscopy 27 Al NMR spectra were measured from SP experiments in the four kinds of pastes as a function of time. Results only for N and NS samples are shown in Figs.…”
Section: (2) 29 Si Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…However, no correlations between aluminum substitution in C-S-H and the chemical composition of the solution were established. A pH dependence was clearly demonstrated by Kwan et al 16 Our purpose in this article was to correlate the concentrations in solution with aluminum substitution in C-S-H, using MASNMR and MQ MASNMR. 27 Al has 2I observable transitions that can be separated into two groups: the central transition (1/2 ↔ −1/2) and the other transitions, often called the external transitions.…”
Section: Introductionmentioning
confidence: 90%
“…C-S-H gel may contain Al, Fe and Mg due to sorption or co-precipitation (Taylor, 1993;Andersen et al, 2003). It is reported that minor components can modify the crystal growth by substitution in the lattice of the calcium silicate hydrates (Kwan et al, 1996;Kulik and Kersten, 2001). Almost all calcium in natural crystalline phases of calcium silicate hydrate such as tobermorite (C 5 S 6 H 5 ) and xonotlite (C 5 S 5 H) can be replaced with heavy metals, for example, cobalt or nickel (Viehland et al, , 1997.…”
Section: Belitementioning
confidence: 99%